Thermal Imaging - Maimunah, Mohd Ali; Norhashila, Hashim; Bernard, Maringgal; Nurazwin, Zulkifli (Springer, Cham, 2024)
Thermal imaging has emerged as a powerful tool in the food industry by offering non-destructive means to assess temperature-related characteristics crucial for quality, safety, and shelf-life evaluations. The acquisition of thermal data is explored, elucidating various techniques utilizing thermal sensors and devices. In this chapter, the thermal properties in food materials and thermal mapping employed for studying acquired data in the context of food analysis are discussed. Several applications of thermal imaging in the food analysis including quality control, shelf-life prediction, and safety assessments are elucidated. Some perspectives on the challenges and future directions of using thermal imaging are addressed. This comprehensive exploration not only underscores the pivotal role of thermal properties and imaging techniques in advancing food analysis, but also sets the stage for emerging research directions in this dynamic field.